(untitled) (Konferensiyalar | Conferences, 2024)
the article focused on the concept of teacher’s meta language, the main key aspects of the meta -language. Moreover, different types of teacher’s meta-language that educators may use in the classroom are described in it. In the field of education using appropriate meta-language in the classroom offers several advantages for both teachers and students, the information about the following advantages are mentioned also in the article.